2022
DOI: 10.1002/jex2.58
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics and biological activity of extracellular vesicles engineered to express SARS‐CoV‐2 spike protein

Abstract: SARS-CoV-2 viral infection led to the devastating COVID-19 pandemic, where illness stemmed from interactions between virions and recipient host cells resulting in multi-layered pathological consequences. The role of the infection portal is now understood to be the cellular angiotensin converting enzyme-2 (ACE2) receptor, which binds to viral spike (S) protein initiating virion internalisation process. Since SARS-CoV-2 virions bear some resemblance to endogenously produced small extracellular vesicles (sEVs) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…However, more recent studies that have separated cell derived particle preparations into their respective constituents using density gradient ultracentrifugation have detected calnexin in EV associated fractions, including in particle preparations derived from HEK293T cells. These studies have shown that calnexin is not as underrepresented as other non‐EV proteins more usually associated with nuclear and mitochondrial processes and post‐translational modification (Choi et al., 2022 ; Kugeratski et al., 2021 ). Furthermore, calnexin has also been suggested as a marker of large EVs (>150 nm) (Théry et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, more recent studies that have separated cell derived particle preparations into their respective constituents using density gradient ultracentrifugation have detected calnexin in EV associated fractions, including in particle preparations derived from HEK293T cells. These studies have shown that calnexin is not as underrepresented as other non‐EV proteins more usually associated with nuclear and mitochondrial processes and post‐translational modification (Choi et al., 2022 ; Kugeratski et al., 2021 ). Furthermore, calnexin has also been suggested as a marker of large EVs (>150 nm) (Théry et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Future studies need to evaluate the adjuvant potential of EV-rS by immunizing mice and to investigate their ability to elicit neutralizing antibodies towards SARS-CoV-2. In this regard, the use of EVs or exosomes as a vehicle to deliver SARS-CoV-2 Spike for vaccination purposes has been proposed and tested in other systems (Choi et al, 2022;Jiang et al, 2022;Cacciottolo et al, 2023a;Cacciottolo et al, 2023b;Kim and Thapa, 2023). In one of those studies, Cacciottolo and colleagues (Cacciottolo et al, 2023a) have expressed the Delta variant Spike linked to the N-terminal of the exosome-specific tetraspanin CD9 by a synthetic transmembrane domain and a secretion signal peptide.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that CD9 may collaborate with TMPRSS2 in cleaving viral fusion glycoproteins and facilitate quick entry of coronavirus (e.g., MERS-CoV) into lung cells [54]. Studies also showed that membrane surface CD9 may also be involved in entry and exit mechanisms in respiratory viruses, including SARS-CoV-2 virus [48,[55][56][57].…”
Section: Role Of Extracellular Vesicles In Covid-19 Diseasementioning
confidence: 99%